2021
DOI: 10.4314/jae.v25i1.3s
|View full text |Cite
|
Sign up to set email alerts
|

Level of Savings among Maize Farmers in Doma Local Government Area of Nasarawa State, Nigeria

Abstract: The study examined level of savings among maize farmers in Doma Local Government Area of Nasarawa State, Nigeria. Multistage sampling procedure was used to select 80 respondents in the study area. Primary data were collected using well-structured  questionnaire. Data were analyzed using descriptive statistics and Multiple Linear Regression. The results show that half of the  respondents (50.0%) were within the age bracket of 21 - 40 years with a mean age of 42 years. Majority (83.8%) of the respondents were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The ratio of gross income to variable cost was 1.557; this is further showing that Sesame production is profitable in the study area for the ratio is greater than 1. This is confirmed by Umar et al (2011) in the study of productivity analysis of Sesame (sesame indicum L.) production under organic and inorganic fertilizers application in Doma LGA, Nasarawa State where it was found that, the average gross returns per hectare by the application of organic fertilizer was N59,640.00 and N89,433.00 by application of inorganic fertilizer. Average total variable costs per hectare for organic and inorganic (fertilizers applied) by farmers were N22,855.00 and N27,682.00, respectively.…”
Section: Gross Margin and Cost Structure In Small Scale Sesame Produc...supporting
confidence: 55%
“…The ratio of gross income to variable cost was 1.557; this is further showing that Sesame production is profitable in the study area for the ratio is greater than 1. This is confirmed by Umar et al (2011) in the study of productivity analysis of Sesame (sesame indicum L.) production under organic and inorganic fertilizers application in Doma LGA, Nasarawa State where it was found that, the average gross returns per hectare by the application of organic fertilizer was N59,640.00 and N89,433.00 by application of inorganic fertilizer. Average total variable costs per hectare for organic and inorganic (fertilizers applied) by farmers were N22,855.00 and N27,682.00, respectively.…”
Section: Gross Margin and Cost Structure In Small Scale Sesame Produc...supporting
confidence: 55%